Pemetaan Sosial terhadap Sumberdaya dan Aksesibilitas Nelayan dalam Kebijakan Pembangunan Wisata Pesisir - Evi Sukmayeti (Society, 2019)
Many fishermen in Indonesia have not fully utilized marine resources properly. However, the government has several ways to improve the welfare of fishermen in other sectors than the fisheries; one of them is connecting between fishermen, coastal and tourism. Meninting of West Lombok is a strategic coastal village for the tourism sector. This village has started to develop tourist destinations since 2011, unfortunately, there is no data on fishermen as a real interest group. This study develops a research pattern on fishing communities which generally discusses the social resources of fishermen and the political aspects of fishing communities separately. This study used a qualitative approach to the social mapping method. Data obtained through interviews and observations of purposively selected informants. The data related to fishermen resources are in maps, followed by an analysis of their accessibility to policy. Spatial aspects strengthen their social resources, interests, and accessibilities to coastal tourism development. The results show that the social resources of fishermen of Meninting Village are unevenly distributed in five dusun (sub-villages). Indicators shown are; capital ownership, mastery of knowledge and skills, ownership of production equipment, use of science and technology, ability to diversify production, fishermen's sociopolitical relations and ability to recognize the economic prospects of coastal tourism. Fishermen who live in areas directly facing the sea have better social resources and firmer interests in coastal development. The accessibility of fishing groups is limited in the development policy. Only fishermen in sub-village located in a coastal area can show themselves as defenders. While the fishermen who live far from the beach tend to be latent or even apathetic. This study recommends the need for other social mapping studies on the characteristics of coastal communities and the need for the government to use the social mapping information of fishing communities to formulate policies that contain regional aspects in coastal tourism development.